Better close to home? Geographical and socioeconomic constraints on gendered educational transitions at the upper secondary level - Prix, Irene (Elsevier, 2025)
Educational decisions are affected by geographical accessibility, which may have far-reaching consequences for young people’s future educational pathways. In this paper, we examine the extent to which geographical distance to educational institutions may moderate young people’s applications to upper secondary education in terms of both the track and the gender-(a)typicality of vocational fields of study they apply to. Our study relies on rich register-based data of complete cohorts of 16-year-olds applying to Finnish upper secondary institutions, linked with geographical information on their closest educational alternatives. We find that travel time to the academic track is more decisive than the distance to vocational schools, with geographical accessibility being more significant for boys’ rather than for girls’ application patterns. Moreover, distance sensitivity varied by social origin, with daughters of low-educated parents and sons of medium-educated parents particularly likely to adjust their upper secondary application to the geographical accessibility of educational alternatives. However, we find some indications that particularly girls from lower-educated social backgrounds are more prepared to consider fields of study not typical for their gender if they are more geographically accessible than key alternatives. No such gender-atypical substitutions were evident among boys. We discuss the implications of these findings in the context of explanatory approaches based on risk aversion and (gender) socialization.